2016
DOI: 10.1093/bioinformatics/btw198
|View full text |Cite
|
Sign up to set email alerts
|

TreeQTL: hierarchical error control for eQTL findings

Abstract: Summary: Commonly used multiplicity adjustments fail to control the error rate for reported findings in many expression quantitative trait loci (eQTL) studies. TreeQTL implements a hierarchical multiple testing procedure which allows control of appropriate error rates defined relative to a grouping of the eQTL hypotheses. Availability and Implementation: The R package TreeQTL is available for download at

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 13 publications
4
34
0
Order By: Relevance
“…We added sex, genotype principal components (maximum of three), and surrogate variables sequentially. After multiple hypothesis correction, the number of eAssociations (defined as a SNP-gene pair that passed hierarchical multiple hypothesis testing by TreeQTL 46 ) increased monotonically as the number of covariates, consistent with our intuition that sva only returns significant and independent surrogate variables. Therefore, we decided to use sex, the top three genotype principal components and all surrogate variables (four and five for glucose and galactose conditions, respectively).…”
Section: Expression Qtl Mapping and Quality Controlsupporting
confidence: 83%
See 1 more Smart Citation
“…We added sex, genotype principal components (maximum of three), and surrogate variables sequentially. After multiple hypothesis correction, the number of eAssociations (defined as a SNP-gene pair that passed hierarchical multiple hypothesis testing by TreeQTL 46 ) increased monotonically as the number of covariates, consistent with our intuition that sva only returns significant and independent surrogate variables. Therefore, we decided to use sex, the top three genotype principal components and all surrogate variables (four and five for glucose and galactose conditions, respectively).…”
Section: Expression Qtl Mapping and Quality Controlsupporting
confidence: 83%
“…To determine the genetic effects on gene expression in fRPE, we used RASQUAL 45 to map eQTL by leveraging both gene-level and allele-specific count information to boost discovery power. Multiple-hypothesis testing for both glucose and galactose conditions was conducted jointly with a hierarchical procedure called TreeQTL 46 . At FDR < 0.05, we found 726 shared, 272 glucose-specific, and 191 galactose-specific eQTL ( Table 1, S10 and S11, Fig.…”
Section: Expression and Splicing Quantitative Trait Loci Discoverymentioning
confidence: 99%
“…Third, cis-pQTLs in linkage equilibrium that did not meet the trans-pQTL significance threshold in Sun et al were identified in a step-forward procedure. To identify additional cis-pQTLs we applied a hierarchical multiple testing correction procedure that has been shown to control the false discovery rate at 5% in expression quantitative trait loci (eQTL) studies 72,73 to the pQTL summary statistics from Sun et al 2018 15 . For each aptamer, P-values within each 1MB of any gene encoding the targeted protein or protein complex were first Bonferroni corrected for the number of tests within that cis window(s) to obtain locally corrected P-values.…”
Section: Mendelian Randomisation Analysesmentioning
confidence: 99%
“…The hierarchical error control methods described in this paper have been implemented as a part of the TreeQTL R package [Peterson, ], available online at http://bioinformatics.org/treeqtl.…”
Section: Softwarementioning
confidence: 99%